Evaluation of anxiolytic-like activity of Vitis vinifera juice in mice - Muhammad Aslam; Nuzhat Sultana (Mashhad University of Medical Sciences, 2016)
Objective: Scientificstudies have shown that Vitis vinifera (V. vinifera) contains flavonoids and stillbenoids. Flavonoids are well known to possess anxiolytic activities. In view of the idea that flavonoids present in V. vinifera could be useful in anxiety, we evaluated anxiolytic-like activity of V. vinifera juice (VVJ). Materials and Methods: Light/dark box and the open field test were used to assess the anxiolytic potential of V. vinifera juice (VVJ). The juice was given orally by gavage at the dose of 4 and 8 mL/kg body weight. Diazepam (1 mg/kg i.p.) was used as the standard drug. Results: It was observed that the juice produced significant and dose dependent increase in the time spent in light cubicle (p